Ultrastructural mitral valve abnormalities in infective endocarditis - R. A. Mukhamadiyarov; A. G. Kutikhin (Кардиоваскулярная терапия и профилактика, 2021)
Aim. Using an original method based on backscattered scanning electron microscopy, to study the structural features of the mitral valve leaflets in infective endocarditis.Material and methods. We examined 9 mitral valves extracted during surgical interventions due to structural malfunction in patients with infective endocarditis (IE). The samples were fixed in buffered paraformaldehyde with osmium tetraoxide postfixation. After dehydration by increasing alcohol concentration and acetone, the samples were placed in epoxy resin. After the resin has polymerized, the samples were ground and then polished to the desired depth. To increase the electronic contrast, the samples were treated with a uranyl acetate alcohol solution during dehydration and with Reynolds' lead citrate after polishing the epoxy blocks. The samples were visualized by backscattered scanning electron microscopy at an accelerating 15-kV voltage.Results. Structural leaflet injuries caused by IE were most pronounced in the central part and the base. Necrotic areas were extensive electron-dense formations located in the central leaflet layers, or displaced towards the ventricular surface. The electron-dense material in the necrotic area was poorly structured and contained individual cells and bacteria. Bacteria were also present outside the necrotic area. Necrotic areas were surrounded by a layer of a modified extracellular matrix, usually covered with a fibrin layer. Among the extracellular matrix fibers, the macrophages, smooth myocytes and fibroblasts was noted. The fibrin layer, in addition to these cells, contained a large number of blood vessels and was often covered with endothelium.Conclusion. Infection of the mitral valve leaflets causes a simultaneous inflammatory response and regeneration activation. Without adequate regulatory factors, the processes of inflammation and connective tissue creation lead to structural and functional leaflet failure. Specific causes may be overgrowth of necrotic and inflammatory areas, edema and fiber orientation disorder, as well as leaflet rupture.